Ptismidae fam. nov. (Coleoptera, Staphyliniformia) from the Lower Cretaceous Lebanese amber. (April 2016) - Kirejtshuk, Alexander G.; Chetverikov, Philipp E.; Azar, Dany; Kirejtshuk, Polina A.
Abstract: Ptisma zasukhae gen et sp. nov. is described from the Lower Cretaceous Lebanese amber and attributed to a new family Ptismidae fam. nov. with unclear position within the infraorder Staphylinoformia, hypothetically in the superfamily Staphylinoidea. This species is characterized by the rather small body size (0.59 mm) and structural similarities with different staphylinoid groups. The particular development of the legs of the new taxa shows some similarities with those of small and medium-sized jumping beetles from the superfamilies Scirtoidea, Buprestoidea, Tenebrionoidea, Chrysomeloidea and Curculionoidea. However, jumping beetles of these groups have strong femora and tibiae with large spurs and thick apical setae only on the posterior legs while P. zasukhae sp. nov. demonstrates such features on both mid and posterior legs. Another particularity of P. zasukhae sp. nov. is the unusual large femoral plate of metacoxae extending behind the suture between ventrites 2 and 3. Strong development of these structures are rare among Coleoptera and occurs in different taxonomic groups without close relationship. The studies were carried out with the usage of usual conventional light microscopy and confocal laser scanning microscopy.